PARTICULATE BONE MATRIX USAGE FOR ALVEOLAR BONE CONSERVATION. A HISTOMORPHOMETRIC STUDY. - Fontana S; Plavnik LM; Filippetti M; Malberti AI (2019)
Different filling materials have been used in an attempt to repair bone loss situations. Objective: The present study aimed to examine the effect of a bone matrix in post-extraction remodelling of the alveolar bone, and to perform a histomorphometric analysis of the residual alveolar ridges in Wistar rats. Material and Methods: Both rat first lower molars were extracted and the right alveoli were filled with particles of a bone matrix with mineral components (MO-UNC) (experimental group, EG). The left alveoli were used as a control group (CG). The animals were sacrificed at 0 hrs, 15, 30 and 60 days after extraction, and the samples were processed. Histological sections were made at the level of the mesial alveolus of the first lower molar. Repair of the alveoli was histologically evaluated and a histomorphometric study of total alveolar volume (TAV), height of the buccal plate (Bh), height of the lingual plate (Lh) and percentage of osseointegration (OI) of the particles was performed to compare the residual ridges of CG with those of the EG. Statistical analysis of the data was performed. Results: In the cases of the experimental group, newly-formed bone tissue was identified around the MO-UNC particles (osseointegration). Histomorphometric data indicate that, at 60 days post-extraction, TAV was significantly greater for EG when compared with CG (p<0.05) and the percentage of osseointegration of the particles increased as a function of time (57.6 %, 90.5% y 95.5%, for EG at 15, 30 y 60 days respectively). Conclusions: The bone matrix (MO-UNC) evaluated in this study is an osteoconductive material that prevents the collapse of post-extraction alveolar bone.